2022
DOI: 10.1002/jemt.24204
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial potential of Loranthus pulverulentus conjugated silver nanoparticles

Abstract: The green method is not only harmonious to our environment but saves time and is comparatively cheaper than other methods. The current study is aimed to synthesize the silver nanoparticles (AgNPs) using the green method by using the leaves of Loranthus pulverulentus Wall (LPW) which functioned as a reducing as well as capping agent. The synthesis of biogenic AgNPs was confirmed by UV-Vis spectroscopy (UV-Vis.), Scanning electron microscopy (SEM), X-ray diffraction (XRD), energy dispersive X-ray (EDX), and Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The green synthetic method of ZnO NPs from Musa acuminata fruit peels is a recent approach that is the explanation of a cheap and eco-friendly methods [11]. Characterization of Zinc oxide Nanoparticles showed that crystallite size is about 25.9 nm when examined by XRD, this result was close to Ali et al [27] who mentioned that the average size was 30-40 nm. The synthesized ZnO nanoparticle formation was confirmed by Atomic Force Microscopy(AFM) was 45 nm, this ratio was close to Elumalai and Velmurugan [28].…”
Section: Biosynthesis Of Zno Nps By Musa Acuminata Fruit Peel Extractsupporting
confidence: 57%
See 1 more Smart Citation
“…The green synthetic method of ZnO NPs from Musa acuminata fruit peels is a recent approach that is the explanation of a cheap and eco-friendly methods [11]. Characterization of Zinc oxide Nanoparticles showed that crystallite size is about 25.9 nm when examined by XRD, this result was close to Ali et al [27] who mentioned that the average size was 30-40 nm. The synthesized ZnO nanoparticle formation was confirmed by Atomic Force Microscopy(AFM) was 45 nm, this ratio was close to Elumalai and Velmurugan [28].…”
Section: Biosynthesis Of Zno Nps By Musa Acuminata Fruit Peel Extractsupporting
confidence: 57%
“…ZnO NPs showed the highest diameter of inhibition zone a concentration of 200 mg/ml of E. coli, K. pneumonia P. aeruginosa S. aureus, and S. epidermidis, reaching (28,27,31,29,26) mm respectively, while the ZnO NPs recorded at concentration 12.5 mg/ml lowest areas of inhibition zone against the same isolates reaching (22,23,24,24,21) mm respectively. The green synthetic method of ZnO NPs from Musa acuminata fruit peels is a recent approach that is the explanation of a cheap and eco-friendly methods [11].…”
Section: Biosynthesis Of Zno Nps By Musa Acuminata Fruit Peel Extractmentioning
confidence: 93%
“…In both cases, best peaks appeared at a neutral pH of 7 as at higher pH (11), peaks shifted toward longer wavelength, indicating agglomeration of particles, so pH 7 is optimized for the synthesis of NPs using leaf extracts of both P. granatum and P. rugosus . Similarly, Subhani et al (2022) also narrated the similar shifting of the spectral bands against various values of pH for the AgNPs prepared from a plant extract. The present study findings are also in accordance with the previous findings of the researchers who endorse the credibility of the current study.…”
Section: Discussionmentioning
confidence: 72%
“…The green fabrication method is not only human‐friendly but also saves time and is comparatively biocompatible and cost‐effective than other approaches (Subhani et al, 2022). Nanotechnology is termed as the manipulations of various matters by chemical or physical approaches to formulate/fabricate novel and tunable nanomaterials with peculiar and modifiable properties for particular applications (Summer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the effect of synthesis parameters is essential for designing efficient metal NPs synthesis methods that facilitate ease of synthesis and purification, scale‐up production, and development of environmentally friendly processes (Kim et al, 2017; Subhani et al, 2022). Three crucial factors significantly influencing the synthesis of AgNPs are the pH of the solution ratio of reducing agent to Ag precursor in the growth solution (Tyagi et al, 2016).…”
Section: Resultsmentioning
confidence: 99%